PENYUSUNAN SISTEM AKUNTANSI PADA PERUSAHAAN MENENGAH (Studi Kasus Pada Ud Bola Mas Mojokerto) - Tesa Loneka Anjarsari; Komarudin Achmad (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study has the objective to analyze the accounting system contained in the UD Bola Mas, completing the corresponded evidence transaction, arranging accounting records as a reference later to design financial statements for UD Bola Mas based on the company's accounting systems theory. This research use a case study with descriptive qualitative approach to the object of the research are focused on the arranging of accounting systems at UD Bola Mas. The analysis results of this study showed that: accounting system contained in the UD Bola Mas still has many lacks, included: the unpretentious evidence transaction, so there is undistinction information from the evidence. In the accounting records there is not yet made the cash book and sorting the cash book, to determine the income and outcome within the company so the impact there is not yet made general ledger, also there is not yet did the arrangement of simple financial about income statement, retained earnings statement, statement of cash flow, statement of financial position, balance sheets and financial statements (CALK) which later can be used with the company as a based for the payment of taxes calculation, as a tool of comparative of the company's decision-making in the future. There are some imperfections that occured because lack of understanding about the importance of sustainability accounting systems in a company. This research is relevant for medium company to improve the accounting system for the purpose could be held effectively and efficiently.  Keywords: Accounting System, Financial Reporting and UD Bola Mas